Situational prison control : crime prevention in correctional institutions - Wortley, Richard (Richard K.) (Cambridge studies in criminology (Cambridge University Press), 2002)
"This book examines the control of problem behaviour in prison from a situational crime prevention perspective. Following the success of situational crime prevention in community settings, Richard Wortley argues that the same principles can be used to help reduce the levels of assault, rape, self-harm, drug use, escape and collective violence in our prison systems. This pioneering new study proposes a two-stage model of situational prevention that moves beyond traditional opportunity-reduction: it attempts to reconcile the contradictory urges to control prison disorder by 'tightening-up' and hardening the prison environment on the one hand, and 'loosening-off' and normalising it on the other